Psychometric properties of the survey work-home interaction nijmegen in Argentinian population - Colasanti, Elena Lucía; Castellano, Estanislao; Lapuente, Lucas; Moretti, Luciana Sofía; Medrano, Leonardo Adrián (Frontiers in Psychology, 2022)
In view of the scarcity of adequate measurement instruments for the assessment of Work-Family/Family-Work interactions, the present study aims to provide evidence of the validity and reliability of the SWING scale in a population of Argentine workers. Method. With a sample of N = 611 workers, internal structure, reliability, and concurrent validity were analyzed. Results. The confirmatory factor analysis showed satisfactory fit indices of the original 4-factor model (χ2 = 647.073, gl = 203, CFI = .93, GFI = .92, NFI = .90, TLI = .92, RMSEA = .05, SRMR = .05, AIC = 557,9, BIC = 821,5). The level of reliability was acceptable (α between .68 to .86, ω = .79 to .89). The relationships of the subscale scores with the engagement and burnout variables were as expected according to previous studies. Discussion. Although further research is required, the results support the use of the instrument in Argentine workers.